Pengaruh pajak tangguhan dan ukuran perusahaan terhadap persistensi laba - Dian Maulita; Dien Sefty Framita (Penerbit Goodwood, 2021)
Purpose: This research aimed to determine the effect of deferred tax and company size on earnings persistence in Indonesia's hotel and tourism companies. Research methodology: This research is associative quantitative research. The analysis technique used multiple linear regression with SPSS VS 20.00 as a tool. The population is hotel and tourism companies listed on the IDX for the 2012-2017 period. Samples were taken based on the purposive sampling technique. Results: The conclusions of this study's results are: (1) Deferred tax has no significant effect on earnings persistence. (2) Firm size has a significant effect on earnings persistence. (3) Deferred Tax and Company Size have a significant effect on Earnings Persistence. Limitation: This research's limitations are the short research period and the company's short scope is the object. It is hoped that further research will be done by replacing or adding other dependents such as cash flow volatility, sales volatility, leverage and increasing the scope of the company under study. Contribution: This research's contribution is that the results of this study can be used as a reference for further researchers and a reference for company management in making decisions. Keywords: Deferred tax, Company size, Profit persistence